BETTER OUTCOME OF HIGH-DOSE CEFTAZIDIME IN HEMATO – ONCOLOGICAL PATIENTS WITH INFECTIONS CAUSED BY EXTENSIVELY DRUG-RESISTANT PSEUDOMONAS AERUGINOSA - Alzbeta Zavrelova; Jakub Radocha; Pavla Paterova; Pavel Zak; Benjamin Visek; Martin Sima (Mediterranean Journal of Hematology and Infectious Diseases)
Background: P. aeruginosa sepsis in immunocompromised patients is serious complication of cancer treatment, especially in case of XDR pathogen.